Analisis Serangan Drone dalam Aksi Counter Terrorism terhadap Hubungan Amerika Serikat dan Pakistan pada Masa Pemerintahan Presiden Barack Obama - Tiolina, Jessica; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
The United States and Pakistan have decided to establish a counter terrorism cooperation since the 9/11 incident. This cooperation was initiated by President George Bush as an effort to fight the terrorists. The United States uses drone attacks in counter terrorism operations because they considered drone as a very effective weapon to reduce the number of victims in an arm conflict. The counter terrorism operations was implemented again during the administration of President Barack Obama. Since elected as president, President Barack Obama increased the number of drone attacks in counter terrorism with a targeted killing strategy. The cooperation which initially went well then experienced high tensions due to drone attacks that killed thousands of people in Pakistan. Drone attacks really affected the relations between the United States and Pakistan during the President Barack Obama’s administration. The result of this research indicated that drone attacks affected the relations between the two countries, the tensions between the United States and Pakistan were generated by the high number of drone attacks.